Suppression of murine autoimmune myocarditis achieved with direct renin inhibition. Issue 3 (September 2016) - Takamura, Chisato; Suzuki, Jun-ichi; Ogawa, Masahito; Watanabe, Ryo; Tada, Yuko; Maejima, Yasuhiro; Akazawa, Hiroshi; Komuro, Issei; Isobe, Mitsuaki
Abstract: Background: The renin angiotensin system (RAS) plays an important role in the pathogenesis of cardiovascular diseases and inflammation. Myocarditis is an inflammatory disease of the heart, and the role of the RAS in its pathophysiology is unknown. Because the direct renin inhibitor, aliskiren, is thought to block RAS completely, we investigated the cardioprotective effect of aliskiren in mice with experimental autoimmune myocarditis (EAM). Methods: A cardiac α-myosin heavy chain peptide was injected in mice on days 0 and 7. Aliskiren 25 mg/kg per day ( n  = 10) or vehicle ( n  = 10) was administered to EAM mice starting on day 0 and the animals were killed on day 21. Results: Aliskiren significantly prevented the progression of left ventricular wall thickening in EAM hearts compared to the vehicle-treated group. Histologically, the inflammatory cell infiltration and fibrosis area ratios in the aliskiren-treated group were lower than that in the vehicle-treated group. Immunohistochemistry revealed that aliskiren suppressed CD4 positive cell infiltration in EAM hearts compared to vehicle. Moreover, aliskiren decreased mRNA levels of interleukin (IL)-2, interferon-γ, tumor necrosis factor-α, and collagen 1. In vitro study showed that aliskiren inhibited T cell proliferation and IL-2 production induced by myosin stimulation. Conclusion: Our results suggest that aliskiren ameliorates EAM by suppressing T-cell activation and inflammatory cytokines, and has potential as a treatment for myocarditis.